User tested : how the world's top companies use human insight to create great experiences - Estes, Janelle; MacMillan, Andy (Andy P.) (Ascent Audio, 2022)
Learn what "customer-centric" really means in this groundbreaking book User Tested delivers an eye-opening and compelling treatment of putting customers back at the center of your business model. In this book, you'll discover why the company that offers the best customer experience always wins, and that real, three-dimensional people can't be reduced to data points on a graph. You'll learn about how dashboards and metrics might look pretty in a report or proposal, but that they're a poor substitute for a solid grounding in how real customers really feel. You'll also find out: - How to apply the customer's perspective at scale throughout your company, driven by your board or executives and filtering up through the grassroots - Applying the customer experience playbook, from sales and marketing to product development and customer engagement - How to connect with customers, gain meaningful feedback, and take action on real human insight Perfect for founders, managers, executives, and business leaders in industries of all kinds, User Tested provides a powerful new perspective on how to bring the true voice of the customer back into decision making.